Cortisol: the villain in Metabolic Syndrome? - Paredes,Sílvia (2014)
Objective This article reviews the state of the art regarding the association between glucocorticoid actions and both obesity and insulin resistance, two main features of the metabolic syndrome. Methods A methodological assessment of the literature on PubMed and SciELO databases was conducted by using the following terms: stress, metabolic syndrome, glucocorticoids, obesity, insulin resistance, hypothalamic-pituitary-adrenal-axis and 11β-hydroxysteroid dehydrogenase. Results Chronic stress, mainly through hypothalamic-pituitary-adrenal axis dysregulation, promotes the accumulation of visceral fat. Reciprocally, obesity promotes a systemic low-grade inflammation state, mediated by increased adipokine secretion, which can chronically stimulate and disturb stress system. This vicious cycle, probably initiated by visceral adipose tissue dysfunction, might be the trigger for the development of metabolic syndrome. Conclusion Given the strong evidences linking glucocorticoid release, obesity and type 2 diabetes, better understanding of the mechanisms underlying this connection might be useful for prevention and treatment of the metabolic syndrome.